Histological and Morphological Study of ‎Cerebrum and Cerebellum of Albino Rats Treated ‎With Antiandrogen Flutamide (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
The present study  was aimed to assess the effects of antiandrogen flutamide on some histological and  morphometric cerebrum and cerebellum tissue for white albino rats, Twenty five male rats were divided into five groups each group contains 5 animals, the first  and  second group regarded as positive and negative control, respectively, while the other groups was treated with flutamide drug orally for 28 days at concentrations of (8, 12, 25 mg/kg/day). Histopathological results  revealed that there is a significant increase in cell number of outer granular layers in cerebrum of the groups treated with 25 mg/kg/day compared to positive and negative control group as well as with other treated groups  cerebrum, also the results of histopathological  pointed that there were no  significant  differences  in cerebellum tissue in all  treated groups . The morphometric results showed  that there were no significant differences in thickness of cerebellar layers among different groups , therefore antiandrogen flutamide can be considered as a testosterone modulator. To determine more precise effect of flutamide on the brain, further studies are needed